2014
DOI: 10.1007/s10995-014-1612-y
|View full text |Cite
|
Sign up to set email alerts
|

Induction Rates and Delivery Outcomes After a Policy Limiting Elective Inductions

Abstract: The purpose of this study was to assess induction rates, maternal, and neonatal outcomes following adoption of a policy prohibiting elective inductions at less than 39 weeks gestation and inductions between 39 and 41 weeks with an unfavorable cervix. A retrospective cohort study of all deliveries greater than or equal to 37 weeks gestation was conducted 1 year prior to through 1 year after implementation of the induction policy. Induction rates before and after the policy were calculated as the primary outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…(39,44) Additionally we added descriptive information on the "rationale for implementation strategy" if available. We found two studies stated, that the publication of a guideline (42,43) was their rationale for the strategy and a systematic review and recommendations from the Registered Nurses' Association of Ontario Toolkit was the rationale of the strategy in another study. (38,47) No other study reported any rationale for their idea of the implementation strategy.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…(39,44) Additionally we added descriptive information on the "rationale for implementation strategy" if available. We found two studies stated, that the publication of a guideline (42,43) was their rationale for the strategy and a systematic review and recommendations from the Registered Nurses' Association of Ontario Toolkit was the rationale of the strategy in another study. (38,47) No other study reported any rationale for their idea of the implementation strategy.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…According to the intervention types listed above we found an audit and feedback in Nicoll et al (40), continuous quality improvement in Dunn et al (38) and a multifaceted intervention in Nicholl et al (41) Moreover the local/regional policies are quality improvement projects without feedback and continuous learning. (37,42,43,45) The 2 studies assessing the impact of the publication of a guideline cannot be allocated to any of these strategies as there is no information if for example staff obtained written information about the guidelines or anything else. (39,44) Additionally we added descriptive information on the "rationale for implementation strategy" if available.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Recently published research 3,4 examining elective induction at 39 weeks has suggested multiple benefits of the intervention, including lower rates of hypertensive disorders and fewer cesareans. This research, in addition to other studies which focused on the relationship between induction and cesarean section, [5][6][7][8][9] has led to considerations of the possible wider use of elective induction to improve outcomes. 10 The multiple studies that have examined inductions in recent years have relied primarily on medical records or administrative data.…”
Section: Introductionmentioning
confidence: 99%